Avaliação das atividades anti-inflamatória, anticoagulante e antiproliferativa do inibidor de quimotripsina das sementes de erythrina velutina (EvCI) - Monteiro, Norberto de Kássio Vieira (2011)
Studies indicate that several components were isolated from medicinal plants, which have antibacterial, antifungal, antitumor and anti-inflammatory properties. Sepsis is characterized by a systemic inflammation which leads to the production of inflammatory mediators exacerbated by excessive activation of inflammatory cells and disseminated intravascular coagulation (DIC), in which the human neutrophil elastase plays an important role in its pathogenesis. Several epidemiological studies suggest that components of plants, especially legumes, can play a beneficial role in reducing the incidence of different cancers. A chymotrypsin inhibitor of Kunitz (Varela, 2010) was purified from seeds of Erythrina velutina (Mulungu) by fractionation with ammonium sulfate, affinity chromatography on Trypsin-Sepharose, Chymotrypsin-Sepharose and ion exchange chromatography on Resource Q 1 ml (GE Healthcare) in system FPLC / AKTA. The inhibitor, called EvCI, had a molecular mass of 17 kDa determined by SDS-PAGE. The purified protein was able to inhibit human neutrophil elastase (HNE), with an IC50 of 3.12 nM. The EvCI was able to inhibit both pathways of HNE release stimulated by PAF and fMLP (75.6% and 65% respectively). The inhibitor also inhibited leukocyte migration in septic mice about 87% and prolonged the time of coagulation and inhibition factor Xa. EvCI showed neither hemolytic activity nor cytotoxicity. EvCI showed a selective antiproliferative effect to HepG2 cell lines with IC50 of 0.5 micrograms per milliliter. These results suggest EvCI as a molecule antagonist of PAF / fMLP and a potential use in fighting inflammation related disorders, disseminated intravascular coagulation (DIC) and cancer